2020
DOI: 10.1177/0363546520909389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tendon Lengthening With Traditional Versus Accelerated Rehabilitation After Achilles Tendon Repair: A Prospective Randomized Controlled Trial

Abstract: Background: Early weightbearing protocols after Achilles tendon repair promote mobilization, yet little is known about their effect on tendon lengthening. Purpose: To evaluate tendon lengthening after Achilles tendon repair with accelerated rehabilitation. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Patients undergoing primary repair for acute Achilles tendon ruptures consented to have tantalum beads placed within the tendon. Patients were randomized into either a traditional (wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 20 publications
5
31
0
Order By: Relevance
“…In combination with the lower achievable height (HR_pos) and comparable values for the total distance, this suggests that the entire range of motion is shifted to more dorsiflexed position following AT rupture and repair. This is in line with the differences in maximum peak torque angle, and it further underlines the alteration of the triceps surae lever arm trajectories described following AT rupture [24,34]. In our view, this adds a novel facet to the interpretation of a functional and structural elongation of the muscle-tendon unit in AT repair.…”
Section: Heel-rise Testsupporting
confidence: 83%
See 1 more Smart Citation
“…In combination with the lower achievable height (HR_pos) and comparable values for the total distance, this suggests that the entire range of motion is shifted to more dorsiflexed position following AT rupture and repair. This is in line with the differences in maximum peak torque angle, and it further underlines the alteration of the triceps surae lever arm trajectories described following AT rupture [24,34]. In our view, this adds a novel facet to the interpretation of a functional and structural elongation of the muscle-tendon unit in AT repair.…”
Section: Heel-rise Testsupporting
confidence: 83%
“…In terms of patients' satisfaction, AT rupture is associated with a highly acceptable outcome averaging midterm Achilles Tendon Rupture Scores (ATRS) above 85/100 [23,24]. Neither rehabilitation scheme (accelerated vs. traditional) nor surgical vs. non-surgical treatment seem to have a significant advantage in the average patient [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The PROMIS instruments are already being used in the evaluation of Achilles tendon disorders. 1 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Further analysis has shown that the repaired Achilles tendon is compliant, but that greater strain results in less effective energy storage, e.g., during hopping tasks [ 20 ]. Additionally, studies reported less plantarflexion and increased dorsiflexion during gait which was linked to tendon stiffness and elongation [ 1 , 9 , 21 ]. An altered neuromuscular activation pattern reflected by the augmented tibialis anterior muscle and soleus muscle co-contraction index has been shown to be present [ 9 ].…”
Section: Introductionmentioning
confidence: 99%